Case Study of Alternative Dispute Resolution for Inheritance Distribution of “Adopted Children and Apostasy Through Mediation” - Sontayati Sihite (ISNU Nine-Star Multidisciplinary Journal, 2024)
This study examines alternatives for resolving inheritance disputes involving adopted children and apostates through mediation in Indonesia. The background of this study is the complexity of inheritance law that arises in cases involving adopted children and apostate heirs, where conflicts often occur between parties due to differences in interpretation of religious and customary law. Mediation is chosen as an alternative to resolve disputes peacefully and efficiently, considering that the litigation process is often time-consuming and expensive and can damage family relationships. The method used in this study is normative juridical with a case study approach. Data were obtained through analysis of court decisions, related legal documents, and interviews with mediators, heirs, and legal practitioners. The results of the study indicate that mediation can be an effective means of reaching a peaceful agreement, taking into account the interests of all parties and maintaining family relationships. The conclusion of this study confirms that mediation can be the main choice in resolving inheritance disputes involving adopted children and apostate heirs. Mediation allows for a fair and mutually beneficial resolution, reduces the potential for prolonged conflict, and maintains family harmony.